Weighted gene co-expression network analysis and CIBERSORT screening of key genes related to m6A methylation in Hirschsprung’s disease - Huang, Jiaqian; Chen, Tingwei; Wang, Junjie; Wang, Zhiqiang; Huang, Shungen (Frontiers in Genetics, 2023)
Hirschsprung's disease (HSCR) is a neural crest disease that results from the failure of enteric neural crest cells (ENCCs) to migrate to the corresponding intestinal segment. The RET gene, which regulates enteric neural crest cell proliferation and migration, is considered one of the main risk factors for HSCR and is commonly used to construct Hirschsprung’s Disease mouse models. m6A modification as an epigenetic mechanism is involved in HSCR. In this study, we analyzed the GEO database (GSE103070) for differentially expressed genes (DEGs) and focused on m6A–related genes. Comparing the RNA-seq data of Wide Type and RET Null, a total of 326 DEGs were identified, of which 245 genes were associated with m6A. Memory B cells in RET Null were significantly higher than that of Wide Type according to CIBERSORT. A Venn diagram was used to identify the key genes in the selected memory B cell modules and DEGs associated with m6A. Enrichment analysis showed that seven genes are mainly involved in focal adhesion, HIV infection, actin cytoskeleton organization and regulation of binding. It is possible that these findings could provide a theoretical basis for molecular mechanism studies of Hirschsprung's disease.